Data of academic scientific production from 1940 to 2014 and input for university quality. Dental faculty of Universidad Nacional Mayor de San Marcos - Moromi-Nakata, Hilda (2015)
In order to contribute to better understanding of the academic scientific production of the Faculty of Dentistry at Universidad Nacional Mayor de San Marcos, we present the numerical longitudinal retrospective production between 1940 - 2014, there are 2,833 Bachelor thesis, 74 MSc, 41 Doctoral and 154 Second Specialization. This information is also a final factual input for indicators of university quality. Potential uses of such a volume of sources of scientific knowledge are suggested.